2021
DOI: 10.1063/5.0041193
|View full text |Cite
|
Sign up to set email alerts
|

Controlling structure of materials derived from spinodally decomposing liquids

Abstract: Arresting morphological evolution of spinodally decomposing heterogeneous mixtures via the addition of colloidal particles has resulted in the discovery of new classes of bicontinuous materials, viz., bicontinuous interfacially jammed emulsion gels (bijels) and most recently bicontinuous intraphase jammed emulsion gels (bipjels). Here, we demonstrate how the extent of particle wettability and particle–particle interactions govern the ultimate structure formed. We present the multi-phase lattice Boltzmann metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Jansen and Harting, 26 using the multi-phase lattice Boltzmann method, demonstrated that the fluid ratio and particle wettability have a crucial effect on the formation of bijel-like structures versus Pickering emulsions. Subsequent simulations 27 have shown how the extent of particle−particle interactions, particle wettability, size, and diffusion determines the microstructure of the bijels in bulk samples and thin fluid films. 28 Recently, several experimental methodologies for preparing the bijel-like structure have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Jansen and Harting, 26 using the multi-phase lattice Boltzmann method, demonstrated that the fluid ratio and particle wettability have a crucial effect on the formation of bijel-like structures versus Pickering emulsions. Subsequent simulations 27 have shown how the extent of particle−particle interactions, particle wettability, size, and diffusion determines the microstructure of the bijels in bulk samples and thin fluid films. 28 Recently, several experimental methodologies for preparing the bijel-like structure have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…For t eq = 10 min, according to Fig. S9B (ESI ‡), b at vertical stage position 15 mm decreased with cycles from 0-2 h (cycles [1][2][3][4][5][6][7][8][9][10][11][12], increased between 2 and 3 h (cycles 13-17), and reached a plateau after 3 h (cycle 18), suggesting…”
Section: Effect Of Multiple Vertical Scanning Cycles On Bme Propertiesmentioning
confidence: 99%
“…Bicontinuous microemulsions (BMEs), consisting of thermodynamically stable nanodomains of water and oil separated by surfactant monolayers, are a unique medium potentially useful for many applications, such as enhanced oil recovery (EOR), [1][2][3] hosting enzyme reactions involving apolar substrates, 4 electrolytes for flow batteries, [5][6][7] templating media for nanomaterials, [8][9][10][11][12] and drug delivery vehicles. [13][14][15] BMEs composed of two immiscible polymers and AB-type block copolymers, the latter serving as surfactant, are employed as solid electrolytes for batteries and other materials.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal particles trapped at fluid-fluid interface can be seen in plethora of systems, such as stabilization of emulsions [1][2][3] , foams 4,5 , bijels [6][7][8][9] and liquid marbles 10,11 . Colloidal particles are spontaneously adsorbed on to the fluid-fluid interface and energetics govern the state of the system to reach a minimum energy as first observed by Ramsden 12 and Pickering 13 .…”
Section: Introductionmentioning
confidence: 99%